2019
DOI: 10.15517/rbt.v67i4.34133
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxic effects of mercury chloride on the Neotropical fish Andinoacara rivulatus (Cichlidae: Cichlasomatini)

Abstract: Understanding the effects of heavy metals in aquatic ecosystems is of significant importance due to their potential to bioaccumulate at various trophic levels and induce damage in DNA. Mercury is considered one of the most dangerous heavy metals, causing chromosomal breakage (clastogenic event) or spindle dysfunction (aneugenic event), that can lead to the formation of encapsulated chromatin into a separate smaller nucleus, generally referred to as a micronucleus. We evaluated the sensitivity of the micronucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 58 publications
1
6
0
5
Order By: Relevance
“…However, the mechanisms responsible for formation of NAs is due to know. Further, various studies have documented that NAs can be induced in response to exposure to genotoxic agents (Braham et al, 2017;De Souza Azevedo et al, 2012;Guilherme et al, 2008;Hoshina et al, 2008;Nirchio et al, 2019). This study provides a proof that NAs may arise in the erythrocytes of sh, Channa punctatus due to oxidative stress induced by HgCl 2 .…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…However, the mechanisms responsible for formation of NAs is due to know. Further, various studies have documented that NAs can be induced in response to exposure to genotoxic agents (Braham et al, 2017;De Souza Azevedo et al, 2012;Guilherme et al, 2008;Hoshina et al, 2008;Nirchio et al, 2019). This study provides a proof that NAs may arise in the erythrocytes of sh, Channa punctatus due to oxidative stress induced by HgCl 2 .…”
Section: Discussionsupporting
confidence: 65%
“…The mechanisms of MN formation, which can be related to clastogenic and aneugenic events and their signi cance are well documented (Chondrou et al, 2018;Decordier et al, 2011;Schmid, 1975;Ueda et al, 1992). Ample numbers of investigations are there which have measured induction of MN by HgCl 2 for genotoxicity measurement in shes (Nagarajan Nagarani et al, 2009;Nirchio et al, 2019;Qureshi, Yaqoob, 2013;Yadav & Trivedi, 2009) On the other hand, very less studies are available for the utilization of other nuclear anomalies in erythrocytes for the assessment of DNA damage in aquatic organisms (De Souza Azevedo et al, 2012). Over past few years, the concurrent analyses of NA and MN frequencies in blood have received consideration in genotoxic studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results agreed with the previous. (22)(23)(24) The micronucleus test, one of the most popular and promising tests of environmental genotoxicity, has served as an index of cytogenetic damage for over 30 years. 25. The increase in micronuclei of red blood cells in the present study of (ctenopharyngodonidella) due to mercury chloride toxicity was identified as a good biological indicator of genetic toxins to monitor the influence of such elements.…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, the mechanism responsible for the formation of NAs is due to knowing. Furthermore, various studies have documented that NAs can be induced in response to exposure to genotoxic agents (Azevedo et al ., 2012; Braham et al ., 2017; Guilherme et al ., 2008; Hoshina et al ., 2008; Nirchio et al ., 2019). This study provides a proof that NAs may arise in the erythrocytes of fish C. punctatus because of oxidative stress induced by HgCl 2 .…”
Section: Discussionmentioning
confidence: 99%